IMPACT OF EXTERNAL BUSINESS ENVIRONMENT FACTORS ON INTERNATIONALIZATION OF LITHUANIAN-BORN GLOBAL COMPANIES - Časas, Ramūnas; Dambrauskaitė, Vilma (Ekonomika, 2011)
The paper examines the external factors that influence the internationalization of the Born Global firms in Lithuania. The identification of such factors is based on M. Porter’s National Diamond model. Theoretical analysis of the model enabled us to distinguish 23 factors as potentially influencing the internationalization of firms. The impact of these factors on Born Global firms was explored upon performing a survey of 50 Lithuanian firms of this sort. The survey results have revealed seven factors as having a positive effect on the internationalization of Lithuanian Born Global firms.